Description of Metateratocephalus bialowieziensis sp. n. (Nematoda, Metateratocephalidae) - Holovachov, O.V. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Описан новый вид Metateratocephalus bialowieziensis Holovachov, sp. n. из Польши, который отличается от других видов рода дорсально изогнутым телом, более длинным ректумом и комбинацией морфометрических признаков. A new species Metateratocephalus bialowieziensis Holovachov, sp. n. from Poland is described. It diffres from other species of the genus by dorsally arcuate body, linger rectum and by combination of morphometric characters.